Assessment of muscular perfusion after oral intake of pre-workout nitric-oxide stimulating supplements by Contrast-Enhanced Ultrasound (CEUS): study protocol for a placebo-controlled, randomized cross-over trial in healthy young males - Doll, Julian; Bürkle, Franziska; Neide, Arndt; Tsitlakidis, Stefanos; Bruckner, Thomas; Schmidmaier, Gerhard; Fischer, Christian (Research Square, 2020)
Background The market for dietary supplements in the sports sector has been growing rapidly for several years, though there is still lacking evidence regarding their claimed benefits. One group is that of nitric oxide increasing supplements, so-called "NO-boosters", which are claimed to improv...